Fear of childbirth and mental health among lesbian, bisexual, transgender and queer people: a cross-sectional study - Sofia Hallström; Hanna Grundström; Anna Malmquist; Matilda Eklind; Katri Nieminen (Taylor & Francis Group, 2022)
Background: Most studies of fear of childbirth (FOC) are conducted on heterosexual cisgender pregnant populations of birth-giving parents. Among lesbian and bisexual women, as well as transgender and queer people (LBTQ), minority stress can add an extra layer to FOC. Gender binary and cisnormative assumptions leave it to the patient to educate and navigate healthcare providers, which can increase mental health problems. Objective: The aim of this study is to compare FOC and mental illness among expecting birth-giving parents and their partners in an LBTQ population. Materials and methods: This cross-sectional study recruited 80 self-identified pregnant LBTQ persons and their 54 non-pregnant partners at a LBTQ specialized antenatal clinic in a large Swedish city of over one million inhabitants. The survey included socio-demographic characteristics, sexual and gender orientation, obstetric history, previous mental health, previous trauma exposure and measures of FOC and mental health. Results: Levels of FOC were significantly higher for the pregnant participants (median W-DEQ 67.5) than for partners (median W-DEQ 60.0). The proportion of severe FOC was higher for pregnant participants (20.3%) than for partners (9.4%), although this difference was not statistically significant. Mental illness was significantly associated with FOC. Conclusion: The results add valuable information to our understanding of the specific needs of pregnant LBTQ people and their partners and may help us to develop healthcare in the future.